Assessment of the main sources of variability of soybean (Glycine max) expeller composition and quality: a field study - Maciel, Gisele; Wagner, Jorge; Juan, Nestor Antonio; San Martino, Silvina; Bartosik, Ricardo Enrique (International Commission of Agricultural and Biosystems Engineering, 2021)
Pairs of soybean seeds and their correspondent expeller samples were collected from ten extrusion-expelling processing plants in Argentina. Seeds were analyzed for proximal composition, bulk moisture content (MC) and individual seed MC. Expeller were analyzed for proximal composition, bulk MC, protein solubility in KOH, expeller urease activity and free fatty acid content. Results indicated that average soybean composition was 136 g/kg MC, 207 g/kg oil and 391g/kg crude protein (CP), while the oil extraction efficiency (OEE) of the process was of 60.7%. The expeller composition was 922 g/kg dry matter (DM), 81g/kg oil and 442 g/kg CP. In soybean seeds, coefficient of variation (CV) of MC was 17.2%, 3.0% for CP and 5.1% for oil, while in SBE CV for DM was 2.9%, 3.9% for CP and 19.7% for oil. A relationship among soybean seed MC, OEE and expeller composition was found. Results of this work indicated that conditioning the soybean MC prior to processing is important not only to maximize OEE, but also to achieve uniform expeller composition and to assure anti-nutritional factors deactivation.